Masaru Shintani: The Making of a Modern Canadian Karate Master - Toth, Robert (Revista de Artes Marciales Asiáticas, 2012)
This article looks at the life of Japanese/Canadian karate pioneer, Masaru Shintani, from his birth in Vancouver, British Columbia, until his death in Kapuskasing, Ontario. After more than thirty years of teaching, Shintani created one of the largest karate organizations in North America with over 27,000 members. Shintani also invented Shindo, a martial art facilitating the use of an ancient weapon, the short stick, with modern techniques. For this article, many of Shintani’s senior students helped to reconstruct his life and explain his complex personality with recollections of their teacher. From the beginning of his karate training in an internment camp, to the eventual achievement of 9th-degree black belt, Masaru Shintani epitomized the modern karate master.